2005
DOI: 10.1007/s00127-005-0927-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of psychiatric and alcohol disorders in Ukraine

Abstract: Prevalence estimates of alcoholism among men and recent depression among women were higher in Ukraine than in comparable European surveys. The results argue for the need to develop and implement educational programs focused on the recognition and treatment of mental and alcohol disorders for the general population, psychiatrists, and general medical providers, who are the main source of mental health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
72
3
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(86 citation statements)
references
References 35 publications
7
72
3
4
Order By: Relevance
“…Os resultados obtidos para as Perturbações de Humor, onde as taxas para o género feminino se realçam com valores muito elevados (72,9%) em relação aos obtidos para o género masculino, vão ao encontro de alguns estudos (Kessler et al, 1996;Bromet, 1999), assim como dos resultados revelados pelos censos 2001. Uma das variáveis que pode explicar esta diferença pode ser a instabilidade familiar, visto que 82% dos utentes que apresentaram esta perturbação apresentaram igualmente instabilidade familiar.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Os resultados obtidos para as Perturbações de Humor, onde as taxas para o género feminino se realçam com valores muito elevados (72,9%) em relação aos obtidos para o género masculino, vão ao encontro de alguns estudos (Kessler et al, 1996;Bromet, 1999), assim como dos resultados revelados pelos censos 2001. Uma das variáveis que pode explicar esta diferença pode ser a instabilidade familiar, visto que 82% dos utentes que apresentaram esta perturbação apresentaram igualmente instabilidade familiar.…”
Section: Discussionunclassified
“…Nos homens o diagnóstico mais comum foi o álcool (26,5%) e as desordens de humor (9,7%). Nas mulheres sobressaíram as desordens de humor (20,8%) e desordens de ansiedade 7,9% (Bromet, 1999).…”
unclassified
“…Epidemiological research in Ukraine suggests that the highest rates of heavy drinking is observed in males aged 26–54 and in females aged 18–25 years (Webb et al 2005). Additionally, Bromet et al (2005) found that although the median age of onset for alcohol use disorder for Ukrainian population was 24 years for both genders, the ratio of drinking men to women was 9:1. Similarly, research from the neighboring with Ukraine Russia demonstrated that male sex was a risk factor for heavy alcohol use (Bobak et al 1999).…”
Section: Risk Factors For Alcohol Usementioning
confidence: 97%
“…Similarly, research from the neighboring with Ukraine Russia demonstrated that male sex was a risk factor for heavy alcohol use (Bobak et al 1999). In addition to age and gender, higher education and adequate income were linked to lower consumption of alcohol drinks in Ukraine (Bromet et al 2005; Webb et al 2005). …”
Section: Risk Factors For Alcohol Usementioning
confidence: 99%
See 1 more Smart Citation